Determinan Faktor Pencegahan Fraud Pada Inspektorat Kota Jayapura - Hanum Hadharoh Nakiya; Syaikhul Falah; Ulfah Rizky Muslimin (Jurnal Akuntansi dan Keuangan Daerah, 2023)
This study aims to examine and analyze the effect of public sector audit, internal auditor competence and organizational justice on fraud prevention at the Jayapura City Inspectorate. The population of this study are employees at Jayapura City Inspectorate office. Sources of data in this study are primary data, which data or information obtained directly through the distribution of questionnaires. The measurement scale used by questionnaire in likert scale. The sampling technique used in this research is simple random sampling. The number of samples used are 52 samples. Data analysis in this study was carried out quantitatively, using multiple linear regression statistical tools (Multiple Linear Regression) with SPSS 26 statistical software. The results obtained are public sector audit implementation, internal auditor competence, organizational justice have a significant effect on fraud prevention at the Jayapura City Inspectorate